Myocardial mineralocorticoid receptor activation by stretching and its functional consequences - Diaz, Romina Gisel (2014)
Myocardial stretch triggers an angiotensin II-dependent autocrine/paracrine loop of intracellular signals, leading to reactive oxygen species-mediated activation of redox-sensitive kinases. Based on pharmacological strategies, we previously proposed that mineralocorticoid receptor (MR) is necessary for this stretch-triggered mechanism. Now, we aimed to test the role of MR after stretch by using a molecular approach to avoid secondary effects of pharmacological MR blockers. Small hairpin interference RNA capable of specifically knocking down the MR was incorporated into a lentiviral vector (l-shMR) and injected into the left ventricular wall of Wistar rats. The same vector but expressing a nonsilencing sequence (scramble) was used as control. Lentivirus propagation through the left ventricle was evidenced by confocal microscopy. Myocardial MR expression, stretch-triggered activation of redox-sensitive kinases (ERK1/2-p90), the consequent Na/H exchanger-mediated changes in pHi (HEPES-buffer), and its mechanical counterpart, the slow force response, were evaluated. Furthermore, reactive oxygen species production in response to a low concentration of angiotensin II (1.0 nmol/L) or an equipotent concentration of epidermal growth factor (0.1 μg/mL) was compared in myocardial tissue slices from both groups. Compared with scramble, animals transduced with l-shMR showed (1) reduced cardiac MR expression, (2) cancellation of angiotensin II-induced reactive oxygen species production but preservation of epidermal growth factor-induced reactive oxygen species production, (3) cancellation of stretch-triggered increase in ERK1/2-p90 phosphorylation, (4) lack of stretch-induced Na/H exchanger activation, and (5) abolishment of the slow force response. Our results provide strong evidence that MR activation occurs after myocardial stretch and is a key factor to promote redox-sensitive kinase activation and their downstream consequences.